Improvement of Managing Collateral Documents for Micro Segment at PT Bank XYZ (The Indonesian Journal of Business Administration, 2021)
Bank XYZ currently has 109 strongrooms spread throughout Indonesia, and strongroom management managed by Retail Credit Operations Group (RCO) and this research will focus on micro segment at RCO Bandung. The factors that influence the strongroom capacity are collateral document storage procedures, systems and human resources. Improper management of collateral documents will have an impact on potential of collateral loss and also cost expansion in the revitalization or opening of a new strongroom. The root cause of lack of strongroom capacity was identified by using CRT. The lack of strongroom capacity is caused by an ineffective document storage model, the systems that have not been integrated and the behavior of employees who disorderly administration in monitoring paid-off debtors. By using the credit file folder, it is estimated that in 2023 strongroom's capacity will be overloaded by 1,241 documents of micro debtors. This is because the systems have not been integrated, so that neither RCO Bandung nor the Micro Unit has been able to monitor which debtors are active and debtors paid-off through the system and also the Micro Unit does not monitor paid-off debtors. By using BCOR, the author can find out the Benefit, Cost, Opportunity and Risk of the solution to be applied. By changing the storage model into a stacking method, it is estimated that the strongroom capacity of RCO Bandung can accommodate documents up to more than 2026 with the remaining strongroom capacity of 17,572 documents of debtors. It is estimated that the systems development will be completed in early 2022, so that both RCO and MBG can monitor the status of debtors and the achievement of the migration of legal documents credit and collateral of micro debtor. Keywords: Strongroom Capacity, CRT, stacking method, systems integration, BCOR.